Correlation research on physical activity and executive function in female college students with subclinical depression - Li, Ping; Alhumaid, Majed M.; Wang, Haiyan; Li, Hai; Zhao, Shanguang (Frontiers in Psychiatry, 2024)
Researchers have found that there may be a correlation between physical activity, executive function, and depression for college students with depression. However, there is limited information available regarding the relationship and interaction between subclinical depression, physical activity, and executive function among college students with subclinical depression. The purpose of this study is to assess the correlation and interaction between subclinical depression, physical activity, and executive function in female college students with subclinical depression. The ActiGraph GT3X was utilized to measure physical activity time, and the colour-word Stroop task was employed to evaluate the executive function of the participants. The findings revealed that female college students with subclinical depression had a significantly lower time for moderate-intensity physical activity compared to healthy female college students. Additionally, the subclinical depression group took significantly longer to complete the colour-word Stroop task compared to the healthy group of female college students. The results of correlation and mediation analyses suggest a negative correlation between BDI-II scores and physical activity time and executive function in female college students with subclinical depression. Moreover, executive function appears to play a partial mediating role in the relationship between physical activity and subclinical depression.